Structural analysis and depth profiling of nanometric SiO2/SRO multilayers. (27th March 2012) - Barozzi, M.; Gennaro, S.; Bersani, M.; Vanzetti, L.; Jestin, Y.; Pucker, G.; Milita, S.; Balboni, R.
<x xml:space="preserve">Abstract</x> Multilayers (MLs) consisting of alternating nanometer‐thick silicon‐rich oxide (SRO) and SiO2 layers are attractive structures to produce Si nanocrystals embedded in SiO2 matrix, with controlled size and distribution. The resulting materials are of great interest for applications in silicon light emitting diodes, memory devices and solar cells. The electro‐optical properties depend strongly on the phase separation process and crystallization of the silicon nanocrystals. In addition to furnace annealing (FA), rapid thermal annealing (RTA) can be used to induce the phase separation process. RTA reduces the thermal budget considerably with respect to FA. Here, we present a study on SiO2/SRO MLs annealed either with RTA or FA. Dynamic SIMS depth profiles were acquired to analyze how the excess silicon distribution is influenced by the annealing and to confirm that the ML structure is maintained during the annealing process. In addition, we used photoelectron spectroscopy (XPS) to analyze the composition of the films and to monitor the phase separation process. The SIMS profiles indicate that the layered structure is stable at all temperatures for both FA and RTA annealing. During annealing the concentration of excess Si increases at the centre of the SRO‐rich layer due to formation of Si‐rich dots. Also, the XPS measurements indicate that 10 s of annealing at 1000 or 1100 °C induces substantial phase separation. Copyright © 2012 John Wiley & Sons, Ltd.